The symmetric and asymmetric impact of trade openness, FDI, foreign aid on income inequality in Somalia: evidence from the ARDL and non-linear ARDL approaches - Abdi Majid Yusuf Ibey; Abdikadir Ahmed Mohamed; Abdikani Yusuf Abdulle; Mahdi Mohamed Omar (Cogent Economics & Finance)
Addressing income disparity is essential to attaining long-term economic development and social fairness, especially in unstable governments, such as Somalia. This assessment, which investigates the period from 1980 to 2022—a period marked by significant political, economic, and social transitions—provides fresh insights into the dynamics of income inequality in Somalia, an area that has received little attention in earlier research. Using ARDL and NARDL models, this study examines the symmetric and asymmetric impacts of foreign direct investment (FDI), trade openness, and foreign aid on income inequality. The findings reveal that trade openness is associated with lower income inequality, with positive shocks narrowing disparities and negative shocks worsening them in both the short and long term. In contrast, foreign aid and FDI show no significant effect. Long-run inequality is significantly worsened by GDP per capita, inflation, and urbanization, while short-term effects are either insignificant or marginal. The study’s results highlight the need for targeted policies supporting trade openness with protections, encouraging sustainable urbanization, and adopting inclusive economic growth measures to minimize inequality. This study offers a comprehensive framework for policymakers to promote sustainable urban development, inclusive inflation control, and effective FDI and aid management, while tailoring growth strategies to ensure equity, redistribution, and reduced income inequality.